Agronegócio sucroenergético e desenvolvimento no Brasil - Eduardo Paulon Girardi (Confins)
In this article we analyze the impacts of the recent territorialization (especially from 2003 to 2013) of the sugar-energy sector in the municipalities of the state of São Paulo, Brazil. In 2003 the Brazilian government resumed the incentive to the sector as part of the strategy of insertion of the country into the world economy through agromineral commodities. The objective was to take advantage of international discussions on sustainable development and to offer the world market the ethanol - a non-fossil fuel - as an alternative to oil. The government also stimulated the internal consumption of this agrofuel, which at present is the main destination of Brazilian ethanol. The increase in demand has caused the industry to double in size in ten years. The state of São Paulo concentrates half of Brazil's sugar-energy agribusiness and accounted half of its recent expansion, turning the landscape into a "sugar cane sea". Many municipalities were heavily impacted by the intensification of the sector. Thus, the focus of our analyzes in this article is on the characteristics of these impacts, their consequences for economic and social development and what are the limits of this model of development based on agribusiness, which is the face of capitalist development in the countryside.